2007
DOI: 10.1007/s00586-007-0473-0
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent vertebral failure after vertebroplasty: a biomechanical study of low-modulus PMMA cement

Abstract: PMMA is the most common bone substitute used for vertebroplasty. An increased fracture rate of the adjacent vertebrae has been observed after vertebroplasty. Decreased failure strength has been noted in a laboratory study of augmented functional spine units (FSUs), where the adjacent, non-augmented vertebral body always failed. This may provide evidence that rigid cement augmentation may facilitate the subsequent collapse of the adjacent vertebrae. The purpose of this study was to evaluate whether the decrease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 20 publications
8
83
0
2
Order By: Relevance
“…Of concern is the increased risk of adjacent vertebral body fractures observed in clinical [4,5] and experimental studies [6][7][8]. Although a recent randomized controlled trial comparing vertebroplasty to conservative treatment [9] found no significant difference in adjacent-level fracture incidence, clinically used poly-methyl-methacrylate (PMMA) cements caused marked changes in load transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of concern is the increased risk of adjacent vertebral body fractures observed in clinical [4,5] and experimental studies [6][7][8]. Although a recent randomized controlled trial comparing vertebroplasty to conservative treatment [9] found no significant difference in adjacent-level fracture incidence, clinically used poly-methyl-methacrylate (PMMA) cements caused marked changes in load transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Such adapted cement materials better preserved the failure strength of augmented functional spine units compared to standard PMMA [7], because failure mostly occurred in the adjacent level. Chevalier et al [15] showed numerically that a decreased elastic modulus of the cement reduced the stresses above/below the cement region while still strengthening the vertebral body.…”
Section: Introductionmentioning
confidence: 99%
“…These filling grades resulted in an average augmentation volume of 5.4 ml for the 16 % filling groups and 11.8 ml for the 35 % augmentation groups. According to the literature, 16 % filling is required to restore the biomechanical properties and 35 % filling is equivalent to endplate-to-endplate filling [32,37,38]. An experienced senior spine surgeon performed a bipedicular VP in each vertebra under fluoroscopic guidance.…”
Section: Methodsmentioning
confidence: 99%
“…It is still under debate whether new vertebral fractures appear more often in patients who received cement augmentation than in conservatively treated patients; some studies support this hypothesis [1,6,7,[27][28][29], while others question it [2,3,26,30]. Reducing the augmentation volume [31], using low-modulus PMMA [32] and prophylactic augmentation of adjacent vertebrae [13,25,33] have been proposed as ways of minimizing the risk of subsequent fractures. In particular, a need for materials with less stiffness has been identified to prevent this adverse effect of VP [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation